Molecular Detection of Neuron-Specific ELAV-Like-Positive Cells in the Peripheral Blood of Patients with Small-Cell Lung Cancer - Vito D’Alessandro; Lucia Anna Muscarella; Massimiliano Copetti; Leopoldo Zelante; Massimo Carella; Gianluigi Vendemiale (Cellular Oncology)
Background: n-ELAV (neuronal-Embryonic Lethal, Abnormal Vision)-like genes belong to a family codifying for onconeural RNA-binding proteins. Anti-Hu-antibodies (anti-Hu-Ab) are typically associated with paraneoplastic encephalomyelitis/sensory neuropathy (PEM/PSN), and low titres of anti-Hu-Ab, were found in newly diagnosed Small Cell Lung Cancer (SCLC). The aim of this study is to develop a sensitive and quantitative molecular real-time PCR assay to detect SCLC cells in peripheral blood (PB) through nELAV-like transcripts quantification.